The Ethics and Practice of Refugee Repatriation - Gerver, Mollie (Edinburgh University Press, 2018)
Mollie Gerver considers when bodies such as the UN, government agencies and NGOs ought to help refugees to return home. Drawing on original interviews with 172 refugees before and after repatriation, she resolves six moral puzzles arising from repatriation using the methods of analytical philosophy to provide a more ethical framework.